Perioperative care following complex laryngotracheal reconstruction in infants and children - Gupta, Punkaj (Medknow Publications, 2010)
Laryngotracheal reconstruction (LTR) involves surgical correction of a stenotic airway with cartilage interpositional grafting, followed by either placement of a tracheostomy and an intraluminal stent (two-stage LTR) or placement of an endotracheal tube with postoperative sedation and mechanical ventilation for an extended period of time (singlestage LTR). With single-stage repair, there may be several perioperative challenges including the provision of adequate sedation, avoidance of the development of tolerance to sedative and analgesia agents, the need to use neuromuscular blocking agents, the maintenance of adequate pulmonary toilet to avoid perioperative nosocomial infections, and optimization of postoperative respiratory function to facilitate successful tracheal extubation. We review the perioperative management of these patients, discuss the challenges during the postoperative period, and propose recommendations for the prevention of reversible causes of extubation failure in this article. Optimization to ensure a timely tracheal extubation and successful weaning of mechanical ventilator, remains the primary key to success in these surgeries as extubation failure or the need for prolonged postoperative mechanical ventilation can lead to failure of the graft site, the need for prolonged Pediatric Intensive Care Unit care, and in some cases, the need for a tracheostomy to maintain an adequate airway.